Pengembangan Usaha B&W Collection Melalui Brand Awareness - Ardila; Renny Christiarini (Cv. Utility Project Solution, 2022)
B&W Collection is one of the MSMEs in Batam City that sells fashion products such as bags, wallets, and watches. Based on the results of observations and interviews with B&W Collection business owners, there are several problems faced by B&W Collection, namely in terms of brand awareness and marketing. The B&W Collection counter does not have an identification sign so customers will have difficulty finding the store or may visit the wrong store. As a result of the absence of a store identity, dissemination of names is quite difficult and very low. The marketing strategy at B&W Collection is also still conventional because it only serves and offers customers who visit Plaza Aviari directly so that the customer coverage is not too broad. Therefore, in carrying out this practical work will implement a digital marketing strategy and build brand awareness at the B&W Collection. The project output consists of creating logos, banners, brochures, catalogs, product photography, registration for Google My Business and Maps accounts, social media accounts, creating e-marketing content, and promotions. The results of implementing the project outcomes were considered quite good. It had a positive impact on the B&W Collection which can be seen from the increase in sales in the last two months, online sales through social media, being able to reach a broader range of customers, and being increasingly recognized by the public.